2010
DOI: 10.5194/acp-10-8997-2010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic adjustment of climatological ozone boundary conditions for air-quality forecasts

Abstract: Abstract. Ten different approaches for applying lateral and top climatological boundary conditions for ozone have been evaluated using the off-line regional air-quality model AURAMS, driven with meteorology provided by the GEM weather-forecast model. All ten approaches employ the same climatological ozone profiles, but differ in the manner in which they are applied, via the inclusion or exclusion of (i) a dynamic adjustment of the climatological ozone profile in response to the model-predicted tropopause heigh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…Using an ozone climatology that includes a climatological tropopause with such models can produce, in effect, spurious stratospheric intrusions as air in the upper troposphere (when the actual tropopause is high) is assigned stratospheric values of ozone (e.g., Makar et al, 2010). The opposite effect can occur when the actual tropopause is low.…”
Section: Trajectory Calculation and Global Ozone Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an ozone climatology that includes a climatological tropopause with such models can produce, in effect, spurious stratospheric intrusions as air in the upper troposphere (when the actual tropopause is high) is assigned stratospheric values of ozone (e.g., Makar et al, 2010). The opposite effect can occur when the actual tropopause is low.…”
Section: Trajectory Calculation and Global Ozone Mappingmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of upper boundary conditions to accurate modeling of tropospheric ozone in regional chemical forecast models Makar et al, 2010, and references therein). The Canadian Global Environmental Multiscale meteorology model (GEM, Côté et al, 1998) has been coupled with the Modelling Air quality and CHemistry (MACH) system (Talbot et al, 2009) to operationally predict tropospheric ozone in a global uniform 1 • × 1 • horizontal resolution.…”
Section: Upper Boundary Conditions For Tropospheric Ozone Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Above 100 hPa (the top of the Logan climatology), ozone values were extrapolated (where necessary) to 50 hPa, assuming a constant gradient of mixing ratio. This configuration (with no sponge layer at the model top, and no mass consistency corrections) was found to provide the best overall performance throughout the troposphere (Makar et al, 2010b). The 42-km domain supplies ozone boundary conditions for the 15-km domain, which in turn supplies them for the 2.5-km domain.…”
Section: Modelsmentioning
confidence: 99%
“…Short-lived chemical tracers have constant low concentration profiles on the boundaries. Ozone boundary conditions make use of monthly 3-D climatology with adjustments for model-predicted tropopause height (Makar et al, 2010b). Thus, meteorological downscaling was applied, but not chemical downscaling.…”
Section: Auramsmentioning
confidence: 99%